(untitled) (Indian Journal of Animal Production and Management, 2024)
Poultry production has undergone an enormous expansion and development during last few decades through advances in genetics, nutrition and husbandry which have resulted in improving the productivity. Consequently, the poultry industry has emerged as one of the most dynamic and fastest expanding segments in animal husbandry. It plays a significant role in providing households with a source of nutritious food, income generation, and livelihood support especially in backyard farming systems. Backyard poultry farming is deeply ingrained in cultural practices and poultry birds have cultural and religious significance. Poultry production in India faces several challenges including limited access to veterinary services, biosecurity issues, vulnerability to diseases and high mortality. This paper briefly discusses the behaviours of indigenous poultry birds, its assessment protocols, concepts and indicators of poultry welfare, international welfare guidelines and regulations. The paper also highlights the poultry welfare standards, welfare issues in India and offers a strategy for the mitigation of poultry welfare problem in India.